The excess insulin requirement in severe COVID‐19 compared to non‐COVID‐19 viral pneumonitis is related to the severity of respiratory failure and pre‐existing diabetes. Issue 3 (11th February 2021) - Lockhart, Sam M.; Griffiths, Harry; Petrisor, Bogdan; Usman, Ammara; Calvo‐Latorre, Julia; Heales, Laura; Bansiya, Vishakha; Mahroof, Razeen; Conway Morris, Andrew
Abstract: Introduction: Severe COVID‐19 has been anecdotally associated with high insulin requirements. It has been proposed that this may be driven by a direct diabetogenic effect of the virus that is unique to SARS‐CoV‐2, but evidence to support this is limited. To explore this, we compared insulin requirements in patients with severe COVID‐19 and non‐COVID‐19 viral pneumonitis. Methods: This is a retrospective cohort study of patients with severe COVID‐19 admitted to our intensive care unit between March and June 2020. A historical control cohort of non‐COVID‐19 viral pneumonitis patients was identified from routinely collected audit data. Results: Insulin requirements were similar in patients with COVID‐19 and non‐COVID‐19 viral pneumonitis after adjustment for pre‐existing diabetes and severity of respiratory failure. Conclusions: In this single‐centre study, we could not find evidence of a unique diabetogenic effect of COVID‐19. We suggest that high insulin requirements in this disease relate to its propensity to cause severe respiratory failure in patients with pre‐existing metabolic disease. Abstract : Our observational study demonstrates that insulin requirements in patients with severe COVID‐19 are associated with severity of respiratory failure and pre‐existing diabetes. When these features were accounted for, there was no difference in insulin requirements in patients with COVID‐19 or non‐COVID‐19 viral pneumonitis.